(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In recent years, competency-based approaches in medical education have gained widespread use. This approach focuses on teaching both theoretical knowledge and practical competencies. The introduction of innovative technologies, simulations, and interactive methods in medical colleges in Uzbekistan helps prepare highly qualified specialists.